Allocation of emission permits based on DEA and production stability. Issue 1 (2nd January 2018) - Wu, Huaqing; Zhang, Dongxu; Chen, Bo; Yang, Min
ABSTRACT: Allocation of emission permits (AEP) is the core issue of emission trading system. The allocation scheme based on data envelopment analysis (DEA) can make all decision-making units efficient or Pareto efficient after allocation. With considering the concept of production stability, this paper proposes a novel DEA model for AEP to generate an allocation scheme. Comparing with the existing approaches, the proposed model provides a more practicable allocation scheme to satisfy production needs. Finally, the novel approach is applied to the data-set of sulphur dioxide emissions from 31 provinces in China and results show some regional characteristics.